PENGARUH MOTIVASI, KOMPENSASI, LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. AJA MEGA PERKASA - Sirri, Ahmad; Aprilia, Lisda (Universitas Nahdlatul Ulama Kalimantan Timur, 2024)
Employee performance is an important thing that needs to be maintained to achieve the goals as expected. The measurement of employee performance is impacted by several factors such as motivation, compensation, and work environment. PT Aja Mega Perkasa is a company engaged in the mining sector that has a role in revenue increase support, regional development, increased economic activity, job creation, and a source of income for the central and regional budgets. in Kalimantan Timur. This research aimed to determine the impact of motivation, compensation, and work environment on employees’ performance at PT Aja Mega Perkasa. The sample was 60 people using saturated Sampling. Data collection techniques were carried out by distributing Questionnaires.The results showed that motivation has no significant impact on employee performance and this was compared inversely with the results of work Environment and employee performance. The significance value (sig) of motivation was 0.122 > 0.05, compensation was 0.045 < 0.05, and work environment was 0.015 < 0.05. Thus, compensation and work environment significantly affect employee performance at PT. Aja Mega Perkasa.